2003
DOI: 10.1021/jo0267910
|View full text |Cite
|
Sign up to set email alerts
|

Dictyodendrins A−E, the First Telomerase-Inhibitory Marine Natural Products from the Sponge Dictyodendrilla verongiformis1

Abstract: Five new alkaloids, dictyodendrins A-E (1-5), were isolated from the Japanese marine sponge Dictyodendrilla verongiformis as telomerase inhibitors. Their structures were elucidated by spectroscopic and chemical methods. Dictyodendrins are tyramine-based pyrrolocarbazole derivatives containing three or four p-hydroxybenzene groups. They inhibited telomerase completely at a concentration of 50 microg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
114
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 19 publications
9
114
0
2
Order By: Relevance
“…1 These alkaloids completely inhibit telomerase at concentration of 50 g/ml and are reported to be the first telomerase-inhibitory marine natural products. They also demonstrated that the sulfate functions of the molecules are essential for the bioactivity as the desulfated compound was completely inactive.…”
mentioning
confidence: 98%
“…1 These alkaloids completely inhibit telomerase at concentration of 50 g/ml and are reported to be the first telomerase-inhibitory marine natural products. They also demonstrated that the sulfate functions of the molecules are essential for the bioactivity as the desulfated compound was completely inactive.…”
mentioning
confidence: 98%
“…The search for natural products in marine and terrestrial environments has led to the discovery of a number of biologically active indole alkaloids which includes the family of dictyodendrins, isolated from a Japanese marine sponge, Dictyodendrilla verongiformis in 2003 [46] (Fig. 1.6).…”
Section: Dictyodendrin a And Dictyodendrin Bmentioning
confidence: 99%
“…Owing to specific binding to the telomeric G-quadruplex structure of the 3’-telomere end and strong telomerase inhibitory activity 2 , it is globally used as the standard substance for in vitro assays 38 . To date, various telomerase inhibitors have been isolated from natural products 911 or developed in organic synthesis studies 1214 , and their activities have been evaluated. However, no compound showing stronger activity than 1 has been found, except for synthetic ( S )-isomer 15 .
Figure 1( A ) The chemical structure of 1 and putative amino acid constitution from the structure.
…”
Section: Introductionmentioning
confidence: 99%